Self-care health behaviors in university students of Health Sciences - Ruiz-Aquino , Mely (2021)
The objective of the study was to identify self-care behaviors in the physical and mental health of university students in Health Sciences during the beginning of the first quarter of 2020. The study involved the use of quantitative methodology, descriptive type and transversal design. The population was 481 university students, being the sample 215, selected probabilistically by strata. A scale of self-care behaviors was applied. Measurements of frequencies and proportions were used. The results reveal that 78.6% (169) show healthy self-care behaviors in the mental health dimension, compared to 56.3% of healthy self-care behaviors in the physical health dimension of self-care. Overall, there was a predominance of healthy self-care behaviors [60.9% (131)]. When comparing the sociodemographic characteristics of the sample under study, according to the types of self-care (healthy/unhealthy), it was found that both women and the group of young people, university students who are dedicated only to study, students of the nursing program and people with cohabitation status, show greater healthy self-care. It is concluded by evidencing the predominance of healthy self-care behaviors in its dimensions: self-care of mental and physical health.